2014
DOI: 10.1155/2014/472391
|View full text |Cite
|
Sign up to set email alerts
|

Interocular Symmetry in Macular Choroidal Thickness in Children

Abstract: Objective. To report interocular differences in choroidal thickness in children using spectral domain optical coherence tomography (SD-OCT) and correlate findings with biometric data. Methods. This observational cross-sectional study included 91 (182 eyes) healthy children aged 6 to 17 years with no ocular abnormality except refractive error. After a comprehensive eye exam and axial length measurement, high definition macular scans were performed using SD-OCT. Two observers manually measured the choroidal thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…This result was consistent with previous reports in both adult and pediatric patients. 5,17,22,24,[27][28][29][30][31][32][33] No statistical correlation between central foveal choroidal thickness and retinal thickness was observed, which is consistent with a previous retrospective adult study. 34 The mean central foveal retinal thickness of the myopic participants in our study was 234 mm, which is very close to the 240 mm mean retinal thickness reported in a former study that was also conducted in Chinese children.…”
Section: Discussionsupporting
confidence: 91%
“…This result was consistent with previous reports in both adult and pediatric patients. 5,17,22,24,[27][28][29][30][31][32][33] No statistical correlation between central foveal choroidal thickness and retinal thickness was observed, which is consistent with a previous retrospective adult study. 34 The mean central foveal retinal thickness of the myopic participants in our study was 234 mm, which is very close to the 240 mm mean retinal thickness reported in a former study that was also conducted in Chinese children.…”
Section: Discussionsupporting
confidence: 91%
“…It has recently been reported that healthy boys have larger macular volumes than girls. 19 In our MS cases, we observed that male sex was associated with larger total macular volumes (0.075 mm 3 , 95% CI = 0.008, 0.14, p = 0.028). In our smaller set of control subjects, we observed a similar point estimate for greater volumes in males (0.077 mm 3 , 95% CI = −0.021, 0.17, p = 0.13) although this did not reach statistical significance.…”
Section: Resultsmentioning
confidence: 54%
“…: volume; GCL: ganglion cell layer; IPL: inner plexiform layer; M/F: male/female. Models for macular metrics with mutual adjustment for the four variables listed: age, history of ON, sex and disease duration. a Macular volumes have been reported to be larger in healthy boys versus girls. 19 …”
Section: Resultsmentioning
confidence: 99%
“…1e4 Previous studies have demonstrated interocular symmetry of choroidal thickness, and interocular difference seems to be correlated with interocular difference of axial length in adults 1,2 and children. 3 However, in our clinical setting, interocular differences of choroidal thicknesses are greater in some individuals, although these patients do not seem to have definite anisometropia. Thus, we investigated the interocular discrepancy in subfoveal choroidal thickness in healthy volunteers with isometropia in this study.…”
mentioning
confidence: 55%